Chediak-Higashi syndrome presenting in the accelerated phase - Subramani Palaniyandi; Umapathy Pasupathy; Latha Ravichandran; Aruna Rajendran; Febe Renjitha Suman; Sasitharan R Prasad (South African Medical Association, 2017)
Chediak-Higashi syndrome (CHS) is an extremely rare autosomal recessive disorder characterised by recurrent pyogenic infections, partial oculocutaneous albinism, and mild bleeding. The most reliable finding that helps in diagnosis is abnormally large granules in leukocytes and other granule-containing cells. Herein we report a case of CHS in a 3-month-old girl who presented to us in the accelerated phase of the disease. The case is reported because of the extreme rarity of CHS presenting in the accelerated phase at diagnosis.